Territorial Distribution of Soviet Industry in Context of Preparation of USSR for a Major War (Late 1920s — Early 1940s) - A. Yu. Davydov (Научный диалог)
The author considers the complex process of preparing the USSR for war in the context of the implementation of “socialist reconstruction” (a term put forward by I. V. Stalin in November 1929), which meant a radical restructuring of the economic sphere and related institutions. The article poses a complex problem that presents a symbiosis of a number of topics — the NEP, industrialization, the construction of socialism in the Stalinist way, preparations for a big war. Comprehending the key trends in the evolution of the modernization breakthrough of the late 1920s — early 1940s, the author points to two stages. The first (actually continuing the NEP) was dominated by the principles of the planned use of resources, the content of the second was reduced to the next assault on socialism. The researcher comes to the conclusion that the damage caused to the national economy turned out to be significant and became the reason for the disproportionality of its development. The document presents evidence of the fallacy of the territorial organization of heavy industry and, above all, the military-defense complex on the eve of June 22, 1941. The cause of the catastrophe of the first period of the Great Patriotic War is revealed in the loss of the most important enterprises located mainly in areas close to the western border.